Investment Support for Sustainable Development of Agricultural Enterprises in Ukraine - Mykhalchyshyna, Larysa; Fostolovych, Valentyna; Lymar, Olena; Lomovskykh, Liudmyla; Zharikova, Olena; Savitska, Svitlana (European Journal of Sustainable Development, 2025)
The article reveals the essence of “investment support of the enterprise”, highlights the specifics of the content of investment support of the enterprise at different levels of management. The main processes of investment (organizational, financial and institutional support) are identified based on the existing approaches to defining enterprise investment processes and their classification. The content of organizational support of investment activity of agricultural enterprises is characterized. The dynamics of capital investments of agricultural enterprises in Ukraine in terms of their size is studied. The problems and directions of its improvement are highlighted taking into account the size of the enterprise. The dynamics of investment activity of agricultural enterprises against the background of economic indicators of the industry and the level of return on investment in agricultural enterprises are analyzed in order to substantiate certain conceptual provisions of the financial support process for sustainable development of agricultural enterprises. The structure of capital investments of agricultural enterprises by sources of financing is analyzed. The main restrictions in the self-financing of investment activity by agricultural enterprises are identified based on the substantiation of own sources of financing for investment activity. The level of capital investments financing in agriculture through bank credits and other loans is studied and the mechanisms of directing budget funds to stimulate credit support of agricultural enterprises are described. Trends in the volume of financial assistance to domestic agricultural producers are highlighted and the main factors influencing the process of state support in the agricultural sector of Ukraine’s economy are substantiated. The problems that limit the implementation of the stimulating function of budgetary agrarian policy in Ukraine are identified. The legal framework for investment support of agricultural enterprises is described. The conclusions are drawn that it is necessary to improve the organizational, financial and institutional support for the investment activities for the sustainable development of agricultural enterprises. Keywords: investment activity, sustainable development, investment support, organizational support, financial support, legal framework agricultural enterprise.